TROP2: as a promising target in lung cancer - Li, Xing-xing; Chen, Jia-li (Frontiers in Oncology, 2025)
Lung cancer (LC) is a significant global health concern, underscoring the need for ongoing research into novel therapeutic modalities. Trophoblast cell surface antigen-2 (TROP2) is overexpressed in tumor tissues and minimally expressed in normal tissues, making it a promising target for cancer treatment. A TROP2-targeted antibody-drug conjugate (ADC) has been approved by the Food and Drug Administration (FDA). This review aims to provide a comprehensive overview of the characteristics of TROP2 and its role in cancer development. It is imperative to acknowledge the significant advancements made in the realm of LC therapy through the development of ADCs that specifically target the TROP2 antigen. The potential of the TROP2-ADC in the treatment of LC is a subject of considerable promise, suggesting a promising future in the therapeutic management of this condition.